2018
DOI: 10.1029/2018gl079103
|View full text |Cite
|
Sign up to set email alerts
|

Purple Auroral Rays and Global Pc1 Pulsations Observed at the CIR‐Associated Solar Wind Density Enhancement on 21 March 2017

Abstract: This paper reports two unique auroral features: postmidnight purple auroral rays and global Pc1 geomagnetic pulsations, observed before the onset of the corotating interaction region (CIR) storm of 21 March 2017, at the beginning of the first campaign of the new Particles and Waves in the Inner magnetosphere using Ground-based network observation (PWING) longitudinal ground network with the Arase satellite. The purple auroral rays were observed from~0315 to 0430 UT (~03-04 magnetic local time) in the northeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 46 publications
3
6
0
Order By: Relevance
“…It is interesting to note that the purple/blue aurora in the present event was observed during a weak geomagnetic storm that occurred in association with the arrival of a CIR. Similar purple/blue auroras associated with the CIR arrival were reported by Shiokawa et al (2018) based on a ground‐based observation at Husafell, Iceland. Shiokawa et al (2019) indicated based on statistical study of purple/blue emission from N 2 + ions at a wavelength of 427.8 nm measured by a photometer over 14 years at Athabasca, Canada, that the 427.8 nm emission exceeds 100 Rayleighs when solar wind speed and density is high.…”
Section: Discussionsupporting
confidence: 85%
“…It is interesting to note that the purple/blue aurora in the present event was observed during a weak geomagnetic storm that occurred in association with the arrival of a CIR. Similar purple/blue auroras associated with the CIR arrival were reported by Shiokawa et al (2018) based on a ground‐based observation at Husafell, Iceland. Shiokawa et al (2019) indicated based on statistical study of purple/blue emission from N 2 + ions at a wavelength of 427.8 nm measured by a photometer over 14 years at Athabasca, Canada, that the 427.8 nm emission exceeds 100 Rayleighs when solar wind speed and density is high.…”
Section: Discussionsupporting
confidence: 85%
“…Such EMIC waves propagate along the field lines and are often observed as Pc 1 pulsations on the ground. The EMIC waves and the Pc 1 pulsations shown in this paper have already been analyzed by Shiokawa et al (). They showed that the Pc 1 pulsations with a similar dominant frequency were observed at subauroral latitudes over a wide local time range from midnight to afternoon sectors (cf.…”
Section: Discussionsupporting
confidence: 61%
“…Thus, 427.8-nm emission of more than 100 R is almost always observed at subauroral latitudes during these high geomagnetic activity times. Shiokawa et al (2018) reported impressive purple auroral rays observed at the arrival of a CIR in the solar wind. In order to investigate response of strong 427.8-nm emissions to such particular characteristics of solar wind and geomagnetic field variations, we made a superposed epoch analysis of solar wind and geomagnetic activity parameters with an epoch time when I 4278 exceeds 100 R. Figure 8 It is interesting to note that the timing that I 4278 becomes more than 100 R is characterized by an increase of solar wind speed and a decrease of the solar wind density for both sunlit and dark ionosphere.…”
Section: 1029/2019ja026704mentioning
confidence: 99%
“…Thus, 427.8-nm emission of more than 100 R is almost always observed at subauroral latitudes during these high geomagnetic activity times. Shiokawa et al (2018) reported impressive purple auroral rays observed at the arrival of a CIR in the solar wind. In order to investigate response of strong 427.8-nm emissions to such particular characteristics of solar wind and geomagnetic field variations, we made a superposed epoch analysis of solar wind and geomagnetic activity parameters with an epoch time when I 4278 exceeds 100 R. Figure 8 shows the result of a superposed epoch analysis for the solar wind parameters (IMF-Bz, and solar wind pressure, speed, and density) and geomagnetic indices (SYM-H and AE indices) over ±3 days relative to the epoch time when the 427.8-nm intensity first exceeded 100 R at the zenith of Athabasca, Canada, for θ s > −24°(a-f) and θ s < −24°(g-l).…”
Section: 1029/2019ja026704mentioning
confidence: 99%
See 1 more Smart Citation